The Role Of National Media In Raising Political Awareness Among University Students In Syria - ناصر, فداء; الأسد, آرام (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research aims to measure the level of political awareness among university students in several Syrian universities, especially after the events and conditions they witnessed during the war, in addition to measuring the degree of commitment of Syrian government channels mentioned in this research based on the standards that regulate media work in its correct manner, the extent of its fulfillment of conditions, its viewing and follow-up rates, and the degree of its influence on students through the questionnaire and by using the descriptive and analytical method in analyzing and testing research hypotheses. The study concluded that there is no statistically significant effect towards the role of the three studied channels in shaping social awareness with the difference of the gender variable, with a presence of an effect of the difference in the university variable at the Syrian TV and Al-ikhbariya only while it does not exist at the Dimashq' Broadcast, also there is no statistically significant effect on the difference of college variable at the Syrian TV and Dimashq' Broadcast, while there is a statistically significant impact on Al-ikhbariya channel.